2007
DOI: 10.1007/s10439-007-9290-1
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic Endothelial Cell eNOS and ET-1 Responses to Asynchronous Hemodynamics are Mitigated by Conjugated Linoleic Acid

Abstract: Although local wall shear stress (WSS) induced by blood flow has been implicated in atherogenesis, another prominent and often neglected hemodynamic feature, circumferential strain (CS) driven by pressure, is induced concurrently. To investigate endothelial cell (EC) responses to pathologic hemodynamics and their possible manipulation by pharmaceuticals, we simulated complete hemodynamic conditions comprised of simultaneous WSS and CS during treatment with conjugated linoleic acid (CLA), a known PPAR (-alpha a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…4,5,[11][12][13]17,22,24,[35][36][37] In endothelial cell hemodynamic studies, dextran is often used to help match values of blood viscosity and density. Despite the known effects of dextran on cells and its use in the isolation of blood components, it is often assumed in endothelial cell hemodynamic studies that the effects of neutral dextran are negligible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5,[11][12][13]17,22,24,[35][36][37] In endothelial cell hemodynamic studies, dextran is often used to help match values of blood viscosity and density. Despite the known effects of dextran on cells and its use in the isolation of blood components, it is often assumed in endothelial cell hemodynamic studies that the effects of neutral dextran are negligible.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we chose a dextran molecular weight in the range used in perfusion dynamic cell studies (MW 135,000), 12 concentrations up to 17.5%, above the range normally used which varies from 1% w/w 16,17 and 9.5% w/w. 12,13,37 Molecular weights up to 2 million and concentration up to 30% w/w have been shown to have a Newtonian behavior. 1,8,43,48 The viscosity values we obtained compare well with literature data, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, coronary arteries have reduced eNOS mRNA levels compared with aortic regions, whereas endothelin mRNA shows an opposite trend (88). Fully reversing shear stress is known to inhibit eNOS activation and NO release while enhancing oxidative stress (125).…”
Section: Differential Effects Of Laminar/oscillatory Shear On Endomentioning
confidence: 99%
“…It found that one widely theorized view of the mode of action of CLAs (Wähle and Rotondo 1999) in reducing atherogenesis (based on some studies of CLA causing cancer cells to lose a degree of their self-adhesion powers), by having CLAs cause a reduction in the ability of unwanted or damaged blood cells, blood products, or blood cellular debris to stick together, was disproven and must now be seen as an unlikely pathway for any purported CLA reductions in cardiovascular inflammation or clotting. An alternative explanatory mechanism-an ability for CLAs to enable blood vessels to withstand adverse blood flow and blood pressure fluctuations as seen in heart attacks and strokes-has since been proposed (Dancu et al 2007). In any case, Eder et al (2003) have demonstrated that CLAs lower the cascade of "damage alarm" substances (like nitrous oxide) in the cells lining the human aorta-an important benefit because their uncontrolled release actually tends to exacerbate rather than improve cardiovascular inflammation.…”
Section: Conjugated Linoleic Acids Cardiovascular Health Atherosclementioning
confidence: 99%